2021
DOI: 10.1021/acsami.1c21089
|View full text |Cite
|
Sign up to set email alerts
|

P3HT-Based Organic Solar Cells with a Photoresponse to 1000 nm Enabled by Narrow Band Gap Nonfullerene Acceptors with High HOMO Levels

Abstract: Three narrow band gap (NBG) acceptors, namely, TTDTC-0F, TTDTC-2F, and TTDTC-4F, were synthesized by introducing a strong electrondonating unit as the central core. The enhanced intramolecular charge transfer endows the three acceptors with high-lying highest occupied molecular orbitals (HOMOs) of ∼−5.20 eV and ultranarrow band gaps (∼1.25 eV). When blended with poly(3hexylthiophene) (P3HT), all organic solar cells (OSCs) exhibited a broad photoresponse from 300 to ∼1000 nm. Among them, P3HT:TTDTC-4F-based dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 52 publications
(82 reference statements)
1
10
0
Order By: Relevance
“…The high LUMO (A) allows the rapid electron transfer from D, and the elevated HOMO (A) is conducive for achieving the narrow optical bandgap for broadening the absorption spectrum of A, which can offer effective charge transport. 38 Previous studies have also demonstrated that V oc can be effectively enhanced by designing D with deeper-lying HOMO levels or A with higher-lying LUMO levels, 39 which is consistent with the analysis results of our prediction model. For the work function of the hole transport layer (WF-HTL) and work function of the electron transport layer (WF-ETL), most points are concentrated at the SHAP value of 0, which means that these two features are not important factors for V oc .…”
Section: Resultssupporting
confidence: 90%
“…The high LUMO (A) allows the rapid electron transfer from D, and the elevated HOMO (A) is conducive for achieving the narrow optical bandgap for broadening the absorption spectrum of A, which can offer effective charge transport. 38 Previous studies have also demonstrated that V oc can be effectively enhanced by designing D with deeper-lying HOMO levels or A with higher-lying LUMO levels, 39 which is consistent with the analysis results of our prediction model. For the work function of the hole transport layer (WF-HTL) and work function of the electron transport layer (WF-ETL), most points are concentrated at the SHAP value of 0, which means that these two features are not important factors for V oc .…”
Section: Resultssupporting
confidence: 90%
“…In order to broaden the absorption range, Li et al designed a narrow band gap NFREA TTDTC-4F by introducing a strong electron-donating thieno[3,2- b ]thiophene (TT) unit as the central core. 44 TTDTC-4F possessed a narrow bandgap of 1.25 eV with an absorption edge around 1000 nm. After device optimization, the P3HT:TTDTC-4F based device achieved a PCE of 7.81% with a higher J sc of 22.5 mA cm −2 .…”
Section: Nfreas With Electron Donating Coresmentioning
confidence: 99%
“…[22][23][24][25][26][27] Among these material design strategies, designing A-D-A type NFSMAs with a narrow band gap is an effective strategy to extend the absorption spectrum and increase the short circuitcurrent (J sc ), and thus improve the PCEs of OSCs based on A-D-A type NFSMAs. [28][29][30][31][32][33] In general, enhancing the electrondonating ability of the donor fused-ring core of the A-D-A type NFSMAs can improve the enhanced intramolecular-charge transfer (ICT) effect, and thereby reduce the band gap of the A-D-A type NFSMAs. For example, Bazan and coworkers designed a new NFSMAs IOTIC-2F by introducing a strong electron-donating group in the donor core of NFSMAs.…”
Section: Introductionmentioning
confidence: 99%